1988
DOI: 10.1128/jb.170.4.1831-1836.1988
|View full text |Cite
|
Sign up to set email alerts
|

Oxacillin-induced inhibition of protein and RNA synthesis in a tolerant Staphylococcus aureus isolate

Abstract: A clinical isolate of Staphylococcus aureus was found to be tolerant (MBC >> MIC) to a number of beta-lactam antibiotics, including oxacillin. Biophotometric analysis showed that a number of concentrations of oxacillin were capable of stimulating rapid cellular lysis in this organism, but the extent of lysis was antibiotic concentration dependent and limited. Cell cultures treated with an antibiotic concentration yielding the maximum rate and extent of lysis were analyzed for protein and RNA synthesis by pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…some genes are being selectively expressed. In an earlier study Jablonski and Mychajlonka [21] showed using one‐dimensional gel electrophoresis, alterations in S. aureus protein synthesis in response to oxacillin. The set of proteins that was observed to be produced in response to the various cell wall‐active antibiotics studied may represent a proteomic signature.…”
Section: Resultsmentioning
confidence: 99%
“…some genes are being selectively expressed. In an earlier study Jablonski and Mychajlonka [21] showed using one‐dimensional gel electrophoresis, alterations in S. aureus protein synthesis in response to oxacillin. The set of proteins that was observed to be produced in response to the various cell wall‐active antibiotics studied may represent a proteomic signature.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of these targets not only causes interference with bacterial growth but also invokes in the cells rapid changes in the pattern of transcription of a large number of genes (11,22,35), suggesting the existence of complex regulatory loops which link a wide variety of steps in metabolism to some steps in cell wall biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that Jablonski and Mychajlonka [28] observed that oxacillin challenge of a tolerant S. aureus caused an initial stimulation of RNA synthesis. The genes induced belonged to functional categories that included amino acid transport and metabolism, carbohydrate transport and metabolism, cell-envelope biogenesis, DNA replication, recombination and repair, post-translational modification, protein turnover and chaperones, signal transduction mechanisms, and transcription.…”
Section: The S Aureus Cell Wall Stress Stimulonmentioning
confidence: 98%
“…A regulon is a network of operons controlled by a common regulatory protein. During this time the response of bacteria to cell wall-active antibiotics came to be viewed as a stress response system [28][29][30].…”
Section: The S Aureus Cell Wall Stress Stimulonmentioning
confidence: 99%